1979
DOI: 10.1177/028418517902000406
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Embolization in a Haemophiliac with Post-Traumatic Renal Haemorrhage

Abstract: Percutaneous transcatheter arterial embolization was performed in a case of severe haemophilia A to control haemorrhage secondary to renal trauma. The treatment proved to be life-saving. Eighteen months follow-up revealed no evidence of hypertension, renal failure or infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Previous case reports or case series of patients who underwent renal artery embolization procedures reported that new-onset hypertension may occur, while renal function was neither well documented nor systematically followed. [8][9][10][11][12][13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The best available evidence for blood pressure and renal function outcomes data in patients who had therapeutic renal artery embolization prior to this study comes from a retrospective study by Jacobson et al, 9 which included 36 patients who had a total of 44 procedures. In that study, 14 of 36 patients (39%) had total or partial nephrectomies; renal artery embolization was a secondary therapeutic procedure, which was used to treat surgical complications, such as postnephrectomy bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports or case series of patients who underwent renal artery embolization procedures reported that new-onset hypertension may occur, while renal function was neither well documented nor systematically followed. [8][9][10][11][12][13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] The best available evidence for blood pressure and renal function outcomes data in patients who had therapeutic renal artery embolization prior to this study comes from a retrospective study by Jacobson et al, 9 which included 36 patients who had a total of 44 procedures. In that study, 14 of 36 patients (39%) had total or partial nephrectomies; renal artery embolization was a secondary therapeutic procedure, which was used to treat surgical complications, such as postnephrectomy bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Several agents have been used to induce thrombosis of the target vessel(s), including metal coils, synthetic particulate materials, ethanol, foam sclerosing agents, acrylic glue, iodized oils, and autologous thrombi. [8][9][10][11][12][13][14][15][16] The long-term effects of renal embolization on hypertension and renal function are not well studied. The safety data are limited to case reports and small uncontrolled case series, some providing evidence that both severe hypertension 4,17 and worsening of renal function may occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, when almost the whole of the intrarenal arterial bed is embolized, even with resorbable materials like blood clots and Gelfoam, it can result in permanent cessation of renal function (5). In our case selective embolization controlled the acute renal bleeding and resulted in restoration of satisfactory function of the kidney.…”
Section: Discussionmentioning
confidence: 61%
“…Gelfoam is an effective embolizing material, even in cases with severe disturbances of blood coagulation, e.g. hemophilia (5). Also Gelfoam particles because of their resorption will allow partial or complete recanalization of the embolized vessel between 21 and 35 days after the procedure (14).…”
Section: Discussionmentioning
confidence: 99%